A low cost and quasi-commercial polymer film chip for high-throughput inertial cell isolation. Issue 12 (25th January 2016) - Zhang, Xinjie; Huang, Di; Tang, Wenlai; Jiang, Di; Chen, Ke; Yi, Hong; Xiang, Nan; Ni, Zhonghua
Abstract : We propose a novel scheme for fast fabrication (<20 minutes) of ultra-low-cost (∼1.5 cents) polymer film chips using laser direct writing and roll-to-roll lamination. Abstract : We propose a novel scheme for fast fabrication (<20 minutes) of ultra-low-cost (∼1.5 cents) polymer film chips using laser direct writing and roll-to-roll lamination. The microchannel architectures of the chip are defined by cutting through grooves within a polyvinyl chloride (PVC) hard film using a UV laser system, and then the patterned film is sealed by two sheets of laminating films through a laminator. To obtain the optimal process parameters for chip fabrication, we systematically analyse the influences of the critical factors of laser ablation and thermal lamination on channel dimensions. As an example application of our polymer chip, we develop an integrated device with high bond strength for the high-throughput inertial isolation of cancer cells from human blood. The experimental results show that our device can successfully isolate high purity cancer cells, proving the potential availability of our polymer film chip for biomedical applications. The advantages of low-cost and fast fabrication make our polymer film chip suitable for both laboratory scale development and industrial batch production.